EXPLORING EYE CARE PRACTICES AND SERVICE UPTAKE AMONG DIABETIC INDIVIDUALS - A STUDY FROM A TERTIARY CARE HOSPITAL IN ABBOTTABAD, PAKISTAN - Obaid Ullah,; Arooba Aurangzeb,; Maira Salam,; Shoaib Ismail,; Faisal , Zainab; Iftikhar Ahmed, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Diabetes mellitus is a leading cause of morbidity and mortality, with many ocular severe complications. This cross-sectional study determined adherence to proper eye care recommendations and regular eye examinations among local diabetic patients and factors associated with non-adherence. Methods: This cross-sectional survey assed the knowledge, attitude, and practices of 200 type I and II diabetic patients. The frequency of patients' regular eye examinations, good knowledge of diabetic eye disease, and measures of the association of periodic eye examination with different variables were calculated. Results: There were 116 (58%) males and 84 (42%) females (mean age=55.28 years, SD=13.928 years). The majority belonged to the lower socioeconomic group with little education. 114 (57%) had never had any eye examination. 107 were unaware of the importance of eye examination. Only 35 (17.5%) had good knowledge, and 146 (73%) patients had poor attitudes towards diabetes. Periodic eye examination was significantly associated with occupation, area of residence, and overall knowledge of diabetic eye complications. In contrast, it had no significant association with gender, type of diabetes, presence of eye symptoms, or presence of other diabetes complications. Conclusion: The knowledge of our local population about diabetic eye disease is very deficient. An extensive campaign of educating diabetic patients about ocular complications is necessary to address this.